Starting a business for dummies - Barrow, Colin (--For dummies., 2014)
Starting your own business is an exciting - and challenging - time. This updated edition of the startup classic shows you how to build a business agile enough to take advantage of emerging trends and opportunities, and sturdy enough to weather any storm. Packed with real-life examples and links to hundreds of valuable resources, Starting a Business For Dummies, 4th Edition gives you what you need to make the leap from employee to successful entrepreneur with confidence. All your favourite, trusted content has been updated including: Laying the groundwork and testing the feasibility of your business idea Writing a winning business plan and finding funding How to operate effectively, including managing your finances and employing people Growing your business and improving performance New content includes: The latest funding schemes, including government funding and crowdfunding Tendering for public sector work Avoiding business cyber-crime Franchising and pop ups Exporting (the government has set a target of doubling the number of exporting companies by 2020) Environmental impact (a recent survey found 77% of SMEs wanted to know how to measure and improve their environmental impact).